Molecular dynamics revealed the effect of epoxy group on triglyceride digestion - Li, Xue; Liu, Yan jun; Nian, Binbin; Cao, Xinyu; Tan, Chin Ping; Liu, Yuanfa; Xu, Yongjiang (Elsevier BV, 2022)
The digestion behavior of epoxy triglyceride, the main cytotoxic product of deep-frying oil, remains unknown, which may affect its biosafety. In this study, epoxy triglyceride (EGT) and triglyceride (GT) were used to reveal the effect of epoxy group on digestion. Digestibility rate analysis showed that the free fatty acids release rate of EGT was slower. To clarify this phenomenon, binding ability with salt ions in digestive juice and particle size were also been studied. Cluster size analysis indicated that epoxy group increased triglyceride particle size, resulting in smaller contact area between EGT and lipase. Interface behaviors displayed EGT decreased binding ability with salt ions in digestive juice. Spectroscopic analysis showed EGT caused the red shift of lipase peak, indicating that epoxy group changed lipase structure. Molecular dynamics simulation suggested EGT leads to loosen lipase structure. In conclusion, this study highlights that epoxy group could weaken the triglyceride digestion.